2018
DOI: 10.1101/465419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bayesian computation through cortical latent dynamics

Abstract: Statistical regularities in the environment create prior beliefs that we rely on to optimize our behavior when sensory information is uncertain. Bayesian theory formalizes how prior beliefs can be leveraged, and has had a major impact on models of perception 1 , sensorimotor function 2,3 , and cognition 4 . However, it is not known how recurrent interactions among neurons mediate Bayesian integration. Using a time interval reproduction task in monkeys, we found that prior statistics warp the underlying structu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 108 publications
(139 reference statements)
1
8
0
Order By: Relevance
“…Our study is therefore conceptually different from the fixed interval or discrimination tasks that have been used in most of the above timing studies. Some studies with monkeys used tasks comparable to ours but focused on intervals lasting only hundreds of milliseconds (Jazayeri and Shadlen, 2015;Sohn et al, 2019). The neural activity in primate parietal and frontal cortices observed in these studies is surprisingly similar to what we found in rodent mPFC.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our study is therefore conceptually different from the fixed interval or discrimination tasks that have been used in most of the above timing studies. Some studies with monkeys used tasks comparable to ours but focused on intervals lasting only hundreds of milliseconds (Jazayeri and Shadlen, 2015;Sohn et al, 2019). The neural activity in primate parietal and frontal cortices observed in these studies is surprisingly similar to what we found in rodent mPFC.…”
Section: Discussionsupporting
confidence: 84%
“…The neural representations of these probability distributions and the mechanism underlying the probabilistic computations has yet to be determined. An interesting solution was recently proposed based on recordings from monkey frontal cortex by Sohn et al (2019). While the animals measured time intervals in a task very similar to ours, frontal cortex activity followed low-dimensional curved state-space trajectories.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…microelectrode arrays and two-photon imaging) made it possible to monitor the activity of neural populations simultaneously (Cohen and Maunsell, 2009; Leavitt et al, 2017; Zohary et al, 1994). At the same time, it is becoming increasingly apparent that major insight about the neurobiological basis of cognition can be gained if one goes beyond studying single and pairwise statistics (Harvey et al, 2012; Khanna et al, 2019; Mante et al, 2013; Murray et al, 2017; Remington et al, 2018; Sadtler et al, 2014; Sohn et al, 2018; Wang et al, 2018). Furthermore, it has been suggested that low-dimensional neural activity patterns can be used to index global brain states, which influence performance on cognitive tasks.…”
Section: Introductionmentioning
confidence: 99%